2003
DOI: 10.1038/sj.ejhg.5200966
|View full text |Cite
|
Sign up to set email alerts
|

PCR-generated padlock probes distinguish homologous chromosomes through quantitative fluorescence analysis

Abstract: Conventional cytogenetic techniques can distinguish homologous chromosomes in a qualitative manner based upon obvious morphological features or using in situ hybridization methods that yield qualitative data. We have developed a method for quantitative genotyping of single-nucleotide variants in situ using circularizable DNA probes, so-called padlock probes, targeting two different alpha satellite repeat variants present in human chromosome 7 centromeres, and a single-nucleotide variation in alpha satellite re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…These probes have detection specificity similar to that obtained with PCR [1][2][3] , but unlike in PCR, the reaction products can remain bound to their target sequences, even withstanding denaturing washes 4 . Unfortunately, detection signals from specifically circularized padlock probes have proven insufficient to reveal single-copy gene sequences owing to background noise from nonspecifically bound probes, although repeated centromeric sequences have been evaluated with sufficient precision to investigate the distribution of single-nucleotide variants in situ 5,6 .…”
mentioning
confidence: 99%
“…These probes have detection specificity similar to that obtained with PCR [1][2][3] , but unlike in PCR, the reaction products can remain bound to their target sequences, even withstanding denaturing washes 4 . Unfortunately, detection signals from specifically circularized padlock probes have proven insufficient to reveal single-copy gene sequences owing to background noise from nonspecifically bound probes, although repeated centromeric sequences have been evaluated with sufficient precision to investigate the distribution of single-nucleotide variants in situ 5,6 .…”
mentioning
confidence: 99%
“…This probe is used for the localization of signals in in situ analyses. For example, a padlock probe was able to detect repeated alphoid sequences in metaphase chromosomes in a living cell, demonstrating its utility for in situ studies [ 53 55 ]. RCA is also known as a simple and efficient isothermal enzymatic process that utilizes strand-displacement DNA and RNA polymerases, like Phi29, Bst, and Vent exo-DNA polymerases for DNA and T7 RNA polymerase for RNA, to generate long single stranded DNAs and RNAs containing tens to hundreds of tandem repeats that are complementary to the circular template [ 56 58 ].…”
Section: Utilization Of Dna Ligases In Genetic Research Technologimentioning
confidence: 99%
“…Christian et al (2001) demonstrated that rolling circle amplification in situ can detect the gene copy number and single base mutations in fixed cells and can also detect and quantify the transcribed RNA in individual cells, making it a versatile tool for cell-based assays. Using the PCR-generated padlock probes, homologous chromosomes were quantitatively distinguished by Antson et al (2003), who observed the transmission of the chromosomes by the in situ analysis during three consecutive generations. According to Zhang et al (2006), the method of amplification of "padlock" probes (sometimes also called C-probes, i.e.…”
Section: Technology Of Polypeptide Nucleic Acidsmentioning
confidence: 99%